The influence of Sn doping on the growth of In2O3 on Y-stabilized ZrO2(100) by oxygen plasma assisted molecular beam epitaxy - Bourlange, A; Payne, D; Palgrave, R; Zhang, H; Foord, J; Egdell, R; Jacobs, R; Veal, T; King, P; McConville, C (2009)
The influence of Sn doping on the growth of In2 O3 on Y-stabilized ZrO2 (100) by oxygen plasma assisted molecular beam epitaxy has been investigated over a range of substrate temperatures between 650 and 900 °C. The extent of dopant incorporation under a constant Sn flux decreases monotonically with increasing substrate temperature, although the n -type carrier concentration in "overdoped" films grown at 650 °C is lower than in films with a lower Sn concentration grown at 750 °C. The small increase in lattice parameter associated with Sn doping leads to improved matching with the substrate and suppresses breakup of the films into square islands observed in high temperature growth of undoped In2 O 3 on Y-stabilized ZrO2 (100). Plasmon energies derived from infrared reflection spectra of Sn-doped films are found to be close to satellite energies in core level photoemission spectroscopy, but for a nominally undoped reference sample there is evidence for carrier accumulation at the surface. This influences both the In 3d core line shape and the intensity of a peak close to the Fermi energy associated with photoemission from the conduction band. © 2009 American Institute of Physics.